EVALUASI KANDUNGAN THEAFLAVIN DAN THEARUBIGIN PADA TEH KERING PADA KEMASAN - Dadan Rohdiana (Jurnal Kimia Terapan Indonesia, 1999)
Theaflavin and thearubigin are important compounds produce by enzymatic oxidation of polyphenol compounds in tea liquor. These compounds influent liquor quality in tea quality, es ecially color annd teste. Among the all Criteria of ea liquor quality value, color and taste.The enzymatic oxidation of polyphenol compounds will continue change theaflavin to thearubigin, so thearubigin content in tea is higher than thaflavin. This research is aimed to evaluated theaflavin and thearubigin content in Indonesian packed tea.Generally tea process manufacturing classified into four groups, i.e: black tea, green tea, jasmine tea and other aroma of tea.Analitical result showed that black tea have higher theaflavin and thearubigin content than green tea and jasmine tea. this case is understandale, because theaflavin and thearubigin is care product polyphenol compounds oxidation, where black tea experienced full of oxidation.